Health-Seeking Behavior of Rural Women with Hypertension to Control Blood Pressure in Purwakarta and Padang Pariaman District - Dainy, Nunung Cipta; Rahman, Purnawati Hustina; Khomsan, Ali; Tanziha, Ikeu; Nurdin, Naufal Muharam; Kasmita, Kasmita (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2021)
Background: The prevalence of hypertension in West Java and West Sumatra are in high level. Hypertension in rural areas tends to be higher than in urban areas, and women are higher than men. The lack of control of blood pressure in people with hypertension and the delay in seeking treatment can increase mortality. Purposes: This study aims to analyze the women’s access to health facilities and health-seeking behavior carried out by women in rural areas. Methods: This study was a cross-sectional method in Purwakarta (Sunda) and Padang Pariaman (Minang) District. There are 75 people each sample women aged 35–55 years with hypertension. Analysis statistic using Pearson Chi-Square. Results: The results show that above 60% of responden chosen Puskesmas became health facilities. Sunda women significantly use doctor’s clinics more than Minang women (p-value 0.05). Most Sunda women changed their behavior by taking antihypertensive drugs and losing weight to controlling blood pressure compared to Minang women (p 0.05). Conclusion: The conclusion, Puskesmas as a main place for treatment and medical-related to control their blood pressure. However, changes in the health behavior of Sunda women prefer to take drugs, and weight loss, while the Minang women tend to reduce salt consumption.